2012
DOI: 10.17159/2413-3051/2012/v23i4a3177
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for local community development in private sector-led renewable energy projects in South Africa: an evolving approach

Abstract: The Renewable Energy Independent Power Producer Procurement Programme in South Africa is intended to support the uptake of renewable energy, help address the current energy supply crisis and mitigate greenhouse gas emissions. Notably, it also requires project developers to engage with socio-economic development at the local level. The distributed nature of renewable energy generation may induce a more geographically dispersed pattern of development, and renewable energy sites can be highly suited to rural loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…As critics have pointed out, this definition presents a number of problems (Baker and Wlokas, 2014;Tait et al, 2013;Wlokas et al, 2012). First, what constitutes a community is not defined, but is treated as an arbitrary geographically delimited object for development intervention.…”
Section: Constructing the 'Community'mentioning
confidence: 99%
See 2 more Smart Citations
“…As critics have pointed out, this definition presents a number of problems (Baker and Wlokas, 2014;Tait et al, 2013;Wlokas et al, 2012). First, what constitutes a community is not defined, but is treated as an arbitrary geographically delimited object for development intervention.…”
Section: Constructing the 'Community'mentioning
confidence: 99%
“…It is too early to assess potential developmental outcomes for 'communities', but recent history suggests the signs are not particularly promising. Working through community trusts is unlikely to change this and REIPPPP is unlikely to deliver meaningful and inclusive change unless there is deeper engagement with beneficiary communities (Wlokas et al, 2012). Working through community trusts is unlikely to change this and REIPPPP is unlikely to deliver meaningful and inclusive change unless there is deeper engagement with beneficiary communities (Wlokas et al, 2012).…”
Section: Conservative Development Visionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mix of electricity generation depended heavily on coal, resulting in 'combined margin emission factor' for South Africa of 0.957 tCO 2 /MWh in 2009/2010 [70]. With increasing shares of renewable energy, which will benefit sustainability in social, economic and environmental dimensions [71][72][73], the official electricity plan projects a 34% decline in CO 2 intensity from 2010 to 2030 [74]. Any increase of emissions is, therefore, likely to be reduced; though the reason for including the programme is its reduction in energy poverty.…”
Section: Extend Access By Grid Electrificationmentioning
confidence: 99%
“…In this context, local content requirements means 'local community empowerment targets', which refer to specific community-based initiatives that directly benefit the community instead of 'economic development' that may include domestic industrialisation and preferential procurement. Local community empowerment targets may include enterprise development, management control, job creation and local ownership (Eberhard et al, 2014;Wlokas et al, 2012;Pegels, 2010). Studies have shown, however, that renewable energy developers, or independent power producers (IPPs), do not deliver on the local community empowerment targets set during the bidding process (Wlokas et al, 2017;Eberhard et al, 2014;Wlokas et al, 2012;Pegels, 2010).…”
Section: Introductionmentioning
confidence: 99%